MdMTA‐mediated m6A modification enhances drought tolerance by promoting mRNA stability and translation efficiency of genes involved in lignin deposition and oxidative stress. Issue 4 (26th March 2022) - Hou, Nan; Li, Chaoshuo; He, Jieqiang; Liu, Yu; Yu, Sisi; Malnoy, Mickael; Mobeen Tahir, Muhammad; Xu, Lingfei; Ma, Fengwang; Guan, Qingmei
Summary: Although the N 6 ‐methyladenosine (m 6 A) modification is the most prevalent RNA modification in eukaryotes, the global m 6 A modification landscape and its molecular regulatory mechanism in response to drought stress remain unclear. Transcriptome‐wide m 6 A methylome profiling revealed that m 6 A is mainly enriched in the coding sequence and 3′ untranslated region in response to drought stress in apple, by recognizing the plant‐specific sequence motif UGUAH (H=A, U or C). We identified a catalytically active component of the m 6 A methyltransferase complex, MdMTA. An in vitro methyl transfer assay, dot blot, LC‐MS/MS and m 6 A‐sequencing (m 6 A‐seq) suggested that MdMTA is an m 6 A writer and essential for m 6 A mRNA modification. Further studies revealed that MdMTA is required for apple drought tolerance. m 6 A‐seq and RNA‐seq analyses under drought conditions showed that MdMTA mediates m 6 A modification and transcripts of mRNAs involved in oxidative stress and lignin deposition. Moreover, m 6 A modification promotes mRNA stability and the translation efficiency of these genes in response to drought stress. Consistently, MdMTA enhances lignin deposition and scavenging of reactive oxygen species under drought conditions. Our results reveal the global involvement of m 6 A modification in the drought response of perennial apple trees and illustrate its molecular mechanisms, thereby providing candidate genes for the breeding of stress‐tolerant apple cultivars.